PENERAPAN METODE NAIVE BAYES PADA APLIKASI PREDIKSI KECANDUAN SESEORANG TERHADAP MEDIA SOSIAL - Livienia Livienia; Viny Christanti Mawardi; Janson Hendryli (PROSIDING SERINA, 2021)
During this pandemic, internet usage is getting higher, both among children, teenagers, and adults. The internet may be used for many functions at some stage in this pandemic, such as school, work, finding information, or even just for entertainment. The most popular internet usage activity is social media. Social media is a medium to socialize with each other and is performed online which allows individuals to have interaction with each other without being constrained by time and space. There are several advantages of social media including that social media means a tool that can be used to publish yourself, work, exclusive opinions, everyday events from yourself. Using public media, communicating online can be done more simply and does not have to be face-to-face. Communication between regions is very possible through social media where one can socialize regardless of distance, time, cost, culture, including gender and age. Social media also has some drawbacks such as excessive use of social media can lead to addiction. However, not many people know whether they have used social media properly or not. Because people in general do not yet know whether the habit of using social media shows addictive behavior or not, a system is designed to be able to predict a person's addiction to social media by applying the Naive Bayes method. This system is based on a social media addiction measurement tool, but this measuring tool can only measure the level of addiction based on a person's behavior. Therefore, this system is designed to be able to predict a person's addiction not only based on behavior but from other factors